PENGGOLONGAN PENDUDUK DALAM PEMBUATAN SURAT KETERANGAN WARIS TERKAIT PENDAFTARAN HAK ATAS TANAH SETELAH BERLAKUNYA UNDANG-UNDANG NOMOR 12 TAHUN 2006 TENTANG KEWARGANEGARAAN REPUBLIK INDONESIA - Ketut Novita Sari; Sihabudin Sihabudin; Bambang Sutjito (Trunojoyo Madura University, 2019)
This research aims at analyzing the classification of citizen in the making of statement of inheritance related to the registration of right over land after the enactment of Law number 12 year 2006 about the Republic of Indonesia citizenship. It also analyzes the legal force of statement of inheritance issued by notary, statement of inheritance issued by Village chief of the head of the district, and the statement of inheritance issued by Balai Harta Peninggalan (the office of inheritance affairs) related to the registration of right over land after the enactment of Law number 12 year 2006 2006 about the Republic of Indonesia citizenship. This research is normative using statute, conceptual, and historical approaches. Data analysis employed Grammatical and historical interpretations The findings of the study show that citizen classification in the making of statement of inheritance still applies as the regulation has not yet been repealed. Regulation for specific group of citizen should not imperatively apply. Whwn the rule is repealed, the regulation becomes alternative of facultative for the citizens of Indonesia. The legal force of statement of inheritance couses problems because the regulation regarding the form of the document is no clear so that it does not qualify to be a perfect evidence.